2019
DOI: 10.1177/0040517519871944
|View full text |Cite
|
Sign up to set email alerts
|

A green method to fabricate porous polypropylene fibers: development toward textile products and mechanical evaluation

Abstract: In this study, a series of immiscible polymer blend fibers with polypropylene (PP) and polyvinyl alcohol (PVA) was obtained by a melt spinning process, and two different draw ratios were attempted. Efforts were made to obtain the porous PP fibers by removing the water-soluble PVA phase. The thermal properties of the blends were tested by thermogravimetric analysis and differential scanning calorimetry. The blends showed excellent thermal stability and differentiated fractionated crystallization behaviors of PP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 49 publications
0
8
0
Order By: Relevance
“…Therefore, the PS phase can act as a model to build microstructure by controlling the shape of PS domains; see the schematic graph in Figure 5 . The spherical and fibril-like bulge structures, grooves [ 15 ], and bundle-like microfiber structure [ 17 ] could be generated on the fiber surface. Usually, these kind of surface-structured fibers are produced by wet-spun [ 44 ], electrospun [ 45 ], how drawing [ 46 ] processes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, the PS phase can act as a model to build microstructure by controlling the shape of PS domains; see the schematic graph in Figure 5 . The spherical and fibril-like bulge structures, grooves [ 15 ], and bundle-like microfiber structure [ 17 ] could be generated on the fiber surface. Usually, these kind of surface-structured fibers are produced by wet-spun [ 44 ], electrospun [ 45 ], how drawing [ 46 ] processes.…”
Section: Resultsmentioning
confidence: 99%
“…Bump structures are observed on the fiber surface due to the rheological behaviors of dispersed phases under the parabolic flow field during melt-spinning, and (sub) micron grooves are observed on the fiber surface after dissolving the second domains. A similar method had been used to fabricate porous structure in PP fibers by selective extraction of Poly (vinyl alcohol) (PVA) from PP/PVA blend fibers [ 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is found that enhanced moisture absorption and air permeability of polyamide (PA) fibers can be achieved due to the high solubility of PEG in water. In the research work performed by Yan et al [62], an immiscible polymer blend with polypropylene (PP) and polyvinyl alcohol (PVA) was made and melt spun into fibers. The porous PP fibers were obtained by taking the water-soluble PVA phase away.…”
Section: Melt Spinningmentioning
confidence: 99%
“…The molten polymer blends were pumped and pushed through two parallel dies with multiple cylindrical holes. A relatively high portion of PVA was removal from the fibers [62,63]. It is noted that other sacrificial polymers may be used to generate the pores.…”
Section: Melt Spinningmentioning
confidence: 99%
“…In Yan's study, a series of immiscible polymer blend fibers with polypropylene (PP) and polyvinyl alcohol (PVA) were obtained by a melt spinning process, and they obtained the porous PP fibers by removing the water-soluble PVA phase. 21 Compared with the traditional method, such as, particle removal method, it is relatively more facile and economical. The pore structure of the materials can be highly penetrable with significantly improved porosity.…”
Section: Introductionmentioning
confidence: 99%